Epidemiology of type 1 diabetes mellitus in the pediatric population in Veneto Region, Italy. Issue 3 (March 2015) - Marigliano, Marco; Tadiotto, Elisa; Morandi, Anita; Sabbion, Alberto; Contreas, Giovanna; Avossa, Francesco; Fedeli, Ugo; Maffeis, Claudio
Highlights Veneto Region is an area with intermediate–high risk of type 1 diabetes mellitus. Prevalence of pediatric T1DM in the Veneto Region is 1.26 cases/1000 subjects. Incidence of pediatric T1DM in the Veneto Region is 16.5/100, 000 person-years. A higher prevalence is reported in the mountainous and rural areas. A peak of incidence is observed in the pre-pubertal and pubertal age group.